PENELITIAN KUALITAS AIR PADA MATA AIR YANG ADA DI DALAM DAN DI LUAR TUBUH BENDUNGAN JATILUHUR PURWAKARTA-JAWA BARAT - Rahmadi Herman Santosa (Bina Teknik Sumber Daya Air, Kementerian Pekerjaan Umum dan Perumahan Rakyat, 2009)
An Acencer water spring with a discharge of 2 4 L/sec. was observed at the underground correlationtunnel of the hydro-electric generator room of the Jatiluhur Dam. Unfortunately this spring was neverutilized. Whereas actual condition of this spring water is of such good quality that Dr. Basuki Hadimulyono,former Director General of the R&D Agency for Ministry of Public Works had assigned the head of theExperimental Station for Water Resources Environment, Research Center of Water Resources, to conduct aresearch on the possible water use. Based on in-situ research, a water spring was not only found inside thedam body but also outside. This water spring generates a discharge of 3 5 L/sec. Results of the researchconcluded that with indicated water discharge, both sources can be utilized continuously without disturbingother parts of the dam body. However, water quality has to be treated in order to meet the drinking watercriteria particularly regarding the excessive content of Manganese and E-Coli